Prevalence and antimicrobial resistance of Salmonella recovered from pig-borne food products in Henan, China. (March 2021) - Jiang, Zenghai; Anwar, Tanveer Muhammad; Peng, Xianqi; Biswas, Silpak; Elbediwi, Mohammed; Li, Yan; Fang, Weihuan; Yue, Min
Abstract: Foodborne disease is one of the most important public health issues worldwide. Food of animal origin is considered as the main vehicle of transmission to humans. Pigs are carriers of numerous foodborne pathogens, including Salmonella which is linked to pork related infection and leads to significant public health concerns, particularly with emerging antimicrobial-resistant clones. Therefore, a continued and enhanced surveillance system of antimicrobial resistance (AMR) pathogens on animal-borne food is essential. This study aims to investigate the prevalence, serovars, and antimicrobial susceptibility pattern of Salmonella isolated from pig-borne food in Henan Province, China. The Salmonella isolates identification were subjected to microbiological culture and PCR assay with positive isolates were assayed for serotyping by slide agglutination test and antimicrobial resistance susceptibility by MIC test. Collectively, a total of 1441 pork and visceral pig products between March and October in 2019 were collected from retail market, we found that 219 (15.1%) were positive for Salmonella isolates from liver (n = 83), bile (n = 19) and pork (n = 117). The highest prevalence of positive Salmonella isolates was observed 25.86% in liver (n = 83/321), followed by 21.84% in bile (n = 19/87), and 11.33% in pork (n = 117/1033). Seventeen different serovars were identified and classified into five serogroups. The most prevalent identified serovar was S . Derby (32.87%), followed by S . Rissen (25.57%) and S . Goldcoast (10.50%). We also found high resistance rate against tetracycline (96.5%), sulfisoxazole (96.3%), followed by amoxicillin (85.2%), ampicillin (84.4%), and streptomycin (83.7%), respectively. An additional investigation of multi-drug resistance pattern (MDR ≥3 antimicrobial classes) indicated that serovar Indiana (n = 13) showed the highest MDR (ACSSuT-AMC-CIP) prevalence (100%), followed by Goldcoast and Derby. Collectively, this study showed considerable diversity among Salmonella isolates in the pig-borne food and highlighted a high prevalence and emerging foodborne MDR clones may increase the frequency of therapeutic failure in the clinical settings. Highlights: S. Derby was predominant serovar in Pig-origin food. All isolated Salmonella exhibited MDR phenotype. S. Indiana showed the wide MDR spectrum for β-lactams.